X-ray shielding by a novel garment woven with melt-spun monofilament weft yarn containing lead and tin particles. Issue 1 (January 2019) - Mirzaei, Majid; Zarrebini, Mohammad; Shirani, Ahmad; Shanbeh, Mohsen; Borhani, Sedigheh
Conventional lead aprons are rather heavy and uncomfortable for the wearer and also crack easily due to bending during both usage and storage. Coating of textiles with certain compounds provides protection against ionizing radiation. However, coated garments may have reduced flexibility and breathability. The principle aim of this study is development of a lightweight textile-based X-ray radiation shielding. The shielding fabric, while capable of significantly attenuating X-rays, relative to current conventional aprons is more intrinsically flexible, breathable, economical, easy to maintain, and crack resistant. Samples of fabrics were woven using melt-spun polypropylene monofilament yarns containing lead and tin particles. Shielding properties of the samples was measured using a high-purity germanium detector. Results showed that the samples composed of higher metal particles concentration and higher metal density and atomic number exhibited higher attenuation capability. Mechanical properties of the samples were evaluated. Furthermore, insignificant changes in the attenuation capability of samples due to abrasion and laundering processes occurred.